(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
Although romantic deception is prevalent in many societies, it may not be readily acceptable to publicly acknowledge approval of acts associated with such deception. This article explores the publicly acknowledged sentiments of viewers of two YouTube channels aimed at the exposure of romantic deceit through two shows for facilitating a “couple switching phones” game. Specifically, we analyse videos where all participants are caught engaging in extra-relationship affairs. Our study reveals a prevailing trend of neutral comments from viewers, indicating a reluctance to openly acknowledge approval or disapproval of the depicted acts. Interestingly, the discussions primarily revolve around tribal issues [specially focused on the Xhosa tribe] rather than focusing on the subject of romantic deception itself.